Integrasi Fintech dan Perbankan Syariah: Membangun Ekosistem Keuangan Digital yang Berkelanjutan - Makki, Mustaqim; Hasan, Zaenol (Journal of Economic and Islamic Research, 2025)
The development of digital technology has spurred the emergence of financial technology (fintech) capable of providing financial services quickly, efficiently, and inclusively.In the context of Islamic finance, Sharia fintech becomes a potential solution to support Sharia banking, especially in reaching communities that have not been optimally served.However, the integration between fintech and Islamic banking still faces several challenges, both in terms of regulation, Sharia compliance, and the readiness of infrastructure and digital literacy of the community.This research is a literature study aimed at examining the opportunities, challenges, and direction of integrating fintech and Islamic banking in building a sustainable digital financial ecosystem.The method used is qualitative analysis of current scientific sources and sharia financial policies.The study results indicate that the integration of fintech and Islamic banking can enhance financial inclusion, promote halal product innovation, and strengthen the economy of the community.However, strengthening governance, synergy between institutions, and Sharia supervision that is adaptive to technology are needed.This study recommends the development of an inclusive sharia digital financial ecosystem, based on sharia principles, and oriented towards sustainability.